Distribution of Crops and Cropping Patterns in Bangladesh (Bangladesh Rice Journal, 2018)
Agricultural land use and distribution of cultivated crops expressed in cropping pattern (CP) constitute the base for increasing produtivity. An in-depth study was conducted on the existing CPs of Bangladesh in each and every upazila (sub-districts) using semi structured questionnaire and data validation by the stakeholder consultation workshop conducted in each of 64 districts. Three hundred and sixteen CPs were identified throughout Bangladesh excluding the very minor ones. Topmost five CPs were only rice containing CPs, which covered 51% of the net cropped area. The most dominant CP was Boro- Fallow-T. Aman covering 27% of net cropped area. Results on major cropwise CPs, location-wise CPs, CP diversity and crop diversity etc are also presented herein.Bangladesh Rice j. 2017, 21(2): 1-55